BUILD SMART VILLAGE THROUGH FARMERS' ASSISTANCE IN TUNGGUL FARMERS GROUP TO INCREASE FARMERS' WELFARE - Muliasari, Risa Martha; Fauzi, Nurul Fathiyah; Anggriawan, Rendy; Rizkina, Fitriana Dina; Arissandi, Muhammad Fitrianto (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Rice is one food crop that has a role in increasing food security. The advantages of rice farming can be obtained by implementing proper management and efficient use of production factors. Gebang is one of the villages in Patrang District, Jember Regency, which has an active and sustainable farmer group for rice farming accompanied by Field Agricultural Extension Officers (PPL). However, during the assistance, the farmer group has never been directed to calculate profits systematically, so it is unknown whether the rice farming carried out is profitable. The farmer group in discussion is the Tunggul Farmer Group member of the Sahabat Farmers Group Association (Gapoktan). The model of this service activity is counseling and assistance in farming bookkeeping. They carried out the service activity in one of the houses of members of the farmer group, namely Mr. Hanan on Teratai Street, Gebang Village, Patrang District, Jember Regency. The participants who attended were 21 people and enthusiastically participated in the counseling. The outreach activities ran smoothly throughout the event. Farmer group members are encouraged to keep books related to their farm income and expenses. This habit is expected during mentoring. The extension material delivered includes the purpose of bookkeeping or recording farming and how to calculate revenue, costs, and profits.